Kolaborativni spletni slovar kot didaktični pripomoček pri poučevanju poljščine kot tujega jezika - Wtorkowska, Maria (Jezik in slovstvo, 2025)
Neologisms are the lifeblood of any language, and new words are created daily through various word-formation processes that not only name things and phenomena, but also reflect social, cultural, and ethical changes. These words are typically recorded in collaborative or participatory online dictionaries, where users suggest entries that are then evaluated and published by editors. An analysis of the Polish Neologism Dictionary, compiled by the Language Observatory at the University of Warsaw, shows that such a vocabulary collection can serve as a valuable and content-rich tool for teaching Polish as a foreign language. A notable feature of this dictionary is its detailed entries, which, in addition to definitions, include extensive information on the words’ origins, frequency of use, and variants. This structure, beyond its explanatory function, also makes the dictionary a unique resource for researching and studying the word-formation processes of new Polish vocabulary.
Keywords: besedotvorje; collaborative on-line dictionary; kolaborativni spletni slovar; neologism; novotvorjenka; Polish language; Polish language as second language; poljščina; poljščina kot drugi jezik; Słownik neologizmów polskich; word formation